Knowledge and attitude of MBBS students regarding organ donation: A study from an institute of national importance of Eastern India - Swayam Pragyan Parida; Prajna Paramita Giri; Debjyoti Mohapatra; Dinesh Prasad Sahu; Madhumita Patnaik; Vikas Bhatia (Wolters Kluwer Medknow Publications, 2022)
Background: The organ donation rate in India is much lower than the developed countries, which leads to long waiting for the recipient. Religious beliefs, misconceptions, and lack of awareness were a few of the reasons. The study was undertaken to assess the knowledge and attitude of undergraduate medical students regarding organ donation. Methodology: The study was conducted in a tertiary care center in eastern India from February to April 2019. A total of 285 undergraduate students were randomly selected and interviewed by using a pretested structured questionnaire. The data were entered and analyzed. Categorical data were presented as proportion or percentages. Results: Among the participants, 98.6% were aware of organ donation and television was the major source of knowledge for most of them. The participants were found to have a good knowledge regarding organ donation. However, their knowledge was poor regarding the legal framework. Despite knowledge, the attitude toward organ donation was poor among the students. Conclusion: Lack of complete knowledge among health-care providers and particularly doctors can affect the organ donation activity. In a country like India, where the organ donation rate is poor, health-care providers need to take initiative to encourage people. The subject of organ donation should be incorporated into the medical curriculum to improve the knowledge of medical students.